Pengaruh Strategi Pemasaran dan Kualitas Pelayanan Terhadap Kepuasan dan Dampaknya Terhadap Loyalitas Konsumen Daerah Wisata Tahura Lapak Jaru di Kabupaten Gunung Mas - Wihelmus Mardo Davinsi; Meitiana Meitiana; Yunikewaty Yunikewaty (Edunomics Journal, 2023)
This study aims to analyze the effect of marketing strategy on loyalty through the satisfaction of the tourist area of ​​Tahura Jaru in Gunung Mas Regency. The method used in this study is explanatory research. The sample of this study amounted to 75 people as respondents. The data were analyzed using descriptive analysis and statistical inferential analysis of the Structural Equation Modeling (SEM) using the Partial least squares approach (SEM-PLS). The results of the study conclude that marketing strategy affects loyalty either directly or through satisfaction. In this relationship satisfaction is a partial mediation (partial mediation). Service quality does not directly affect loyalty, but through satisfaction. In this relationship satisfaction is a full mediation variable (full mediation). Communication has a significant effect on performance either directly or indirectly.